Ferroptosis: The Silver Lining of Cancer Therapy - Tang, Zhengming; Huang, Zhijie; Huang, Yisheng; Chen, Yuanxin; Huang, Mingshu; Liu, Hongyu; Ye, Q. Adam; Zhao, Jianjiang; Jia, Bo (Frontiers in Cell and Developmental Biology, 2021)
Regulatory cell death has been a major focus area of cancer therapy research to improve conventional clinical cancer treatment (e.g. chemotherapy and radiotherapy). Ferroptosis, a novel form of regulated cell death mediated by iron-dependent lipid peroxidation, has been receiving increasing attention since its discovery in 2012. Owing to the highly iron-dependent physiological properties of cancer cells, targeting ferroptosis is a promising approach in cancer therapy. In this review, we summarised the characteristics of ferroptotic cells, associated mechanisms of ferroptosis occurrence and regulation and application of the ferroptotic pathway in cancer therapy, including the use of ferroptosis in combination with other therapeutic modalities. In addition, we presented the challenges of using ferroptosis in cancer therapy and future perspectives that may provide a basis for further research.